International Trade and Social Connectedness - Michael Bailey; Abhinav Gupta; Sebastian Hillenbrand; Theresa Kuchler; Robert Richmond; Johannes Stroebel (Center for Economic Studies and ifo Institute (CESifo), 2020)
We use anonymized data from Facebook to construct a new measure of the pairwise social connectedness between 180 countries and 332 European regions. We find that two countries trade more with each other when they are more socially connected and when they share social connections with a similar set of other countries. The social connections that determine trade in each product are those between the regions where the product is produced in the exporting country and those where it is used in the importing country. Once we control for social connectedness, the estimated effect of geographic distance on trade declines substantially, and the effect of country borders disappears. Our findings suggest that social connectedness increases trade by reducing information asymmetries and by providing a substitute for both trust and formal mechanisms of contract enforcement. We also present evidence against omitted variables and reverse causality as alternative explanations for the observed relationships between social connectedness and trade flows.
Keywords: F10; F50; F60; 330; international trade; social connectedness; contract enforcement; information frictions